Detached or Interventionist? Comparing the Performance of Watchdog Journalism in Transitional, Advanced and Non-democratic Countries. (January 2020) - Márquez-Ramírez, Mireya; Mellado, Claudia; Humanes, María Luisa; Amado, Adriana; Beck, Daniel; Davydov, Sergey; Mick, Jacques; Mothes, Cornelia; Olivera, Dasniel; Panagiotu, Nikos; Roses, Sergio; Silke, Henry; et al.
This study proposes the interventionist and the detached orientations to watchdog journalism through the conceptual lens of journalistic role performance. Based on a content analysis of 33, 640 news stories from sixty-four media outlets in eighteen countries, we measure and compare both orientations across different countries using three performative aspects of monitoring: intensity of scrutiny, voice of the scrutiny, and source of the event. Our findings show that the interventionist approach of watchdog journalism is more likely to be found in democracies with traditionally partisan and opinion-oriented journalistic cultures or experiencing sociopolitical crises. In turn, the detached orientation predominates in democracies with journalistic traditions associated to objectivity. Although both orientations have a lower presence in transitional democracies, the detached watchdog prevails, while in non-democratic countries the watchdog role is almost absent. Our results also reveal that structural contexts of undemocratic political regimes and restricted press freedom are key definers of watchdog role performance overall. However, the type of political regime is actually more important—and in fact the most important predictor— for detached than for interventionist reporting.